Development of a 3D-printed cervical collar using biocompatible and sustainable polylactic acid - Narayan Yeole Shivraj; Prakash Kode Jaya; Sai Mokka Tharun; Sridhar Babu Bathini; Devana Sudheer Reddy (Journal of the Mechanical Behavior of Materials)
Cervical collars are orthotic devices that are recommended for those patients who suffer from neck discomfort, ailments, and trauma. These braces provide stability and support to the neck as well as keep the head in an upright position. Commercially available collars are found to be uncomfortable, restrictive, and inadequately tolerated. The conventional making of a customized collar is a laborious process that involves casting, sculpting, and molding of thermoplastic materials, which may lead to extreme discomfort. Persistent use of these collars may result in deterioration, which could result in frequent visits to the hospital and increased costs. In order to mitigate these issues, this study delved into the design, analysis, and 3D printing of a customized cervical collar prototype. 3D printing helps in the creation of lightweight, customizable, and cost-effective devices, ensuring a comfortable fit and enhancing remedial efficacy. A computed tomography scan of the neck region of a male patient was utilized. This process consisted of transforming the CT scan data of the neck region to STL file format for achieving a 3D CAD model. In order to ascertain the designed model’s strength, the model was subjected to static linear assessment by applying external loads ranging from 50 to 200 N. The stress pattern in the model was dispersed equally. The analytical results conformed to the material strength criteria, i.e., to a maximum stress of 25.448 MPa with a factor of safety of 3. A customized prototype of the cervical collar weighing 60.58 g was 3D printed utilizing polylactic acid, a biodegradable and sustainable material, on a fused deposition modeling-based 3D printer. The substantiated cervical collar prototype is expected to demonstrate better comfort, adjustability, and overall effectiveness compared to conventional off-the-shelf collars, thereby offering promising prospects for enhanced case care and rehabilitation.